Human immunodeficiency virus (HIV) specific antibodies among married pregnant women and female commercial sex workers attending voluntary counseling and HIV testing (VCT) centre in Abuja, Nigeria (2009)
Generally, married women and commercial sex workers (CSWs) engage in sexual activity - an important risk factor for contracting HIV. We therefore tested a hypothesis that prevalence of HIV-1/2 antibodies among married pregnant women (PW) is not different from that of female CSWs. One hundred married PW and 99 female CSWs enrolled in the study. They were consecutively selected as they visited the VCT centre for HIV antibody test. Pertinent data were obtained from each subject using questionnaire forms; venous blood sample was aseptically collected from subjects that gave verbal consent. Plasma obtained from each sample was tested using parallel testing algorithm with DETERMINE® HIV-1/2 and HIV-1/2 STAT-PAK® test was used for statistical analysis of the data. The overall prevalence of HIV-1/2 antibodies was 29.1% (n = 199). Seroprevalence of 39.4 and 19.0% were observed for the CSWs and the PW, respectively. Using various variables, comparison of HIV-1/2 serostatus of the CSWs with that of the married PW showed that the CSWs generally had significantly higher seroprevalence. CSWs who were inconsistent in the use of condom with their clients prior to sexual intercourse in the past three months before this study (P = 0.0001, OR = 11.2) and those aged _ 39 years had significantly (P =0.004, OR = 2.6) higher seroprevalence. Though both groups recorded seropositivity, inconsistency in the use of condom appeared to be the factor mostly responsible for the significantly higher seropositivity of the female CSWs.